Blue a history of the color as deep as the sea and as wide as the sky - Brew-Hammond, Nana Ekua (Alfred A. Knopf, 2022)
This picture book follows one color's journey throughout history -- from ancient Afghan painters to 1905, when a chemical blue dye was created -- and around the world, as it becomes the blue we know today
Keywords: Blue / Juvenile literature; Pigments / Juvenile literature; Color / Juvenile literature; Dyes and dyeing / Juvenile literature; Blue; Pigments; Dyes and dyeing; Color; Bleu / Ouvrages pour la jeunesse; Pigments / Ouvrages pour la jeunesse; Couleur / Ouvrages pour la jeunesse; picture books; JUVENILE NONFICTION / Art / History; JUVENILE NONFICTION / Concepts / Colors; JUVENILE NONFICTION / People & Places; Color / Psychological aspects / Juvenile literature; Picture books; History; Juvenile works; Pictorial works; Creative nonfiction; Informational works; Illustrated works; Documents d'information; Essais fictionnels; Livres d'images; Ouvrages illustrés; Bilderbuch; Sachbilderbuch